Satisfaction with Digital Financial Services in the Majene District SME Sector - Syamsuddin, Fajar Rakasiwi; Samsuardi Said; Dirmansyah Darwin; Saddam Husain Tamrin (Jurnal Informasi dan Teknologi, 2024)
Advances in technology and information have affected life, especially in the business world. Technology includes a complex process involving people, processes, ideas, tools, and organizations to analyze problems, find solutions, and manage solutions with specific goals. The use of digital financial services can improve people's welfare by increasing economic activity, but the level of digital financial literacy in Indonesia is still low. This study aims to measure the use and satisfaction of the MSME sector in Majene Regency with digital financial services. A mixed-method approach with Descriptive Statistics and Ordinary Least Square (OLS) methods was used to analyze data from 165 MSMEs in Majene Regency. The results show that perceived benefits (X1) and ease of use (X2) have a significant influence on digital financial service satisfaction (Y). Partial and simultaneous tests show a significant effect of the independent variables on the dependent variable. The coefficient of determination shows that the independent variables explain most of the variation in the dependent variable. In conclusion, perceived benefits and ease of use significantly affect satisfaction with digital financial services in Majene Regency MSMEs. Therefore, improving digital financial literacy and ease of use of these services is essential to increase MSME adoption and satisfaction with digital financial services. The government and digital financial service providers need to collaborate to provide adequate education and training to MSMEs to maximize the potential of these services in supporting local economic development.